The Impact of Microfinance on Women Empowerment: A Case Study of the Family Bank, Gezira State, Sudan (2016-2017) - Mustafa, Rajaa H.; Mohamed, Fatima O.; Elgali, Mohamed B. (Gezira Journal of Economic and Social Sciences; مجلد 10 عدد 2 (2019), 2020)
The impact of microfinance on women’s empowerment remains debatable. While some studies suggest that microfinance helps women increasing their income earning abilities, leading to greater power within the household, others think that it may also lead to a more vulnerable position for woman. This study aims to evaluate empirically the impact of microfinance on women’s empowerment in Gezira State taking the Family Bank, Wad Medani Branch as a case study. A sample of 117 women who are clients of the bank were randomly selected for data collection. Descriptive statistics were used to analyze the main features of women under study. Then, the impact of microfinance on women’s empowerment is examined and analyzed through a cross sectional impact methodology, referred to as the control group method. Microfinance borrowers are compared to (soon -to-be microfinance borrowers) and the difference between these two groups is attributed to the acquisition of microfinance. An econometric analysis is then employed on the data gathered via the questionnaire. The results confirm that microfinance has a significant positive impact on women’s empowerment. Furthermore, the variables of women social status, education level and number of children in the household have a positive significant effect on the level of women empowerment in the study area. The, results emphasized that there is a room for empowerment through the microfinance programs, therefore, this study recommends for more improvements in various aspects related to the arrangements and provision of the microfinance from the financial institutions side. لا يزال تأثير التمويل الاصغر على تمكين المرأة موضع جدال. بينما تشير بعض الدراسات إلى أن التمويل الاصغر يساعد النساء على زيادة قدراتهن على كسب الدخل، مما يكسبهن مزيداً من القوة داخل الأسرة، يعتقد آخرون أنه قد يؤدي أيضا إلى وضع أكثر ضعفا بالنسبة للمرأة. تهدف هذه الدراسة إلى إجراء تقييم تطبيقي لتأثير التمويل الاصغر على تمكين المرأة في ولاية الجزيرة مع أخذ  بنك الأسرة فرع ودمدني كحالة دراسة ميدانيه . تم جمع  البيانات عن طريق الاستبيان باختيار عينة عشوائية من 117 امرأة من عميلات البنك لجمع البيانات. و تم استخدام الإحصاء الوصفي لتحليل السمات الرئيسية للنساء قيد الدراسة. كما تم فحص تأثير التمويل الاصغر على تمكين المرأة وتحليله من خلال منهجية تأثير المقطع العرضي، والتي يشار إليها باسم طريقة المجموعة الضابطة. حيث تتم مقارنة المقترضات بالآتي: سيحصلن على القرض قريباً ويعزى الفرق بين هاتين المجموعتين إلى التمويل الاصغر. تم تطبيق تحليل الانحدار الخطي المتعدد على البيانات التي تم جمعها عن طريق الاستبيان. أظهرت النتائج أن التمويل الأصغر له تأثير معنوي إيجابي على تمكين المرأة. علاوة على ذلك، فإن لمتغيرات الحالة الاجتماعية ومستوى التعليم للمرأة وعدد الأطفال في الأسرة تأثير  معنوي ايجابي  على مستوى تمكين المرأة في منطقة الدراسة. وأكدت النتائج أن هناك مجالاً للتمكين من خلال برامج التمويل الأصغر، لذلك توصي هذه الدراسة بمزيد من التحسينات في مختلف الجوانب المتعلقة بتنظيم وتقديم مثل هذه  القروض من جانب المؤسسات التمويلية.